Hubungan Frailty dengan Kesintasan Satu Tahun pada Pasien Lanjut Usia dengan Tumor Padat Ganas Stadium Lanjut - Satrio, Trian; Rizka, Aulia; Prasetyawaty, Findy; Widhani, Alvina; Dwimartutie, Noto; Anggoro, RM Suryo; Yulianti, Mira; Antono, Dono (UI Scholars Hub, 2025)
Introduction. Frailty is characterized by a multisystem physiological decline that increases the risk of morbidity and mortality, especially in patients with advanced-stage solid malignancies. The association between frailty and one-year survival in older adults with solid malignancies in Indonesia has not yet been established. This study aimed to assess the association between frailty status and one-year survival in elderly patients with advanced-stage solid tumors. Methods. This was a retrospective cohort study conducted at Dr. Cipto Mangunkusumo National General Hospital, Jakarta utilizing patient data from a previous study conducted between November 2020 and 2021. Subjects were cancer patients aged >60 years with advanced-stage solid tumors. Frailty was assessed using the FRAIL scale, and one-year survival was determined through medical records and direct follow-up confirmation. Data analysis included bivariate tests, Kaplan-Meier survival analysis, log-rank test, and multivariate Cox regression. Results. A total of 106 elderly patients with advanced solid tumors were analyzed, with a frailty prevalence of 41.5%. A total of 44.3% of patients died within one year. Multivariate analysis showed that frailty was a significant independent predictor of survival. Frail patients had a 2.131 times higher risk of death. Other factors such as nutritional status, polypharmacy, and comorbidities were not significant. Conclusion. Frailty was identified as a significant independent predictor of reduced one-year survival in elderly patients with advanced-stage cancer.